2008
DOI: 10.1055/s-2007-993775
|View full text |Cite
|
Sign up to set email alerts
|

Paeonol and Paeoniflorin, the Main Active Principles of Paeonia albiflora, Protect the Heart from Myocardial Ischemia/Reperfusion Injury in Rats

Abstract: The aim of this study was to investigate the effects of paeoniflorin (PF) and paeonol (PN), the main active compounds of the Paeonia albiflora Pallas, on myocardial ischemia and reperfusion (I/R)-induced injury in Sprague-Dawley rats IN VIVO. Under anesthesia, the rats were subjected to 25 min of ischemia by ligation of the left anterior descending coronary artery (LAD) followed by 6 h (Western blot analysis) or 24 h (hemodynamics and infarct size) of reperfusion. When the infarct size was measured as the perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 15 publications
(21 reference statements)
0
51
0
Order By: Relevance
“…[27][28][29] Previous studies have demonstrated that TSA can protect the brain from I/R injury. 30,31) However, whether TSA has a neuroprotective effect against apoptosis remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] Previous studies have demonstrated that TSA can protect the brain from I/R injury. 30,31) However, whether TSA has a neuroprotective effect against apoptosis remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Tanshinol possess the protection for myocardial mitochondrial membranes and microcirculatory disturbance from ischemia-reperfusion injury (Zhao et al, 1996;Han et al, 2008). And Nizamutdinova et al (2008) had also reported that paeoniflorin could protect the heart from myocardial ischemia/reperfusion injury when high-dosage paeoniflorin was given by peritoneal injection in rats. In the present study, FAT had slight or moderate effect on infarct size and PE had no effect, when given alone by gavage to AMI in the dosage of GXII (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The content of these water-soluble FATPE components in GXII is relatively high. FATE are all effective against myocardial ischemia (Huang et al, 1996;Zhao et al, 1996;Liu et al, 2006;Han et al, 2008;Nizamutdinova et al, 2008). FATPE of GXII were used to test the ABC hypothesis via bioethnopharmaceutical analytical pharmacology (BAP) (Huang, 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…1) is the principal bioactive component of Paeoniae radix which has been used for >1,000 years in traditional Chinese medicine (11). In modern pharmacological studies, PF exhibits numerous pharmacological effects such as anti-inf lammation, antioxidant, endothelium-dependent vasorelaxation, neuromuscular blocking and cognition enhancement properties (12,13).…”
Section: Introductionmentioning
confidence: 99%